The Effectifeness of Joesin Translation Channel on Students' Vocabulary Mastery - Syamsinar Syamsinar; Nur Alim; Ray Suryadi Hasyim; Misbahuddin Misbahuddin; Indrayani Simpuruh (CV. Pusdikra Mitra Jaya, 2023)
This research presented The Effectiveness of Joesin Translation YouTube Channel on Students' Vocabulary Mastery at SMP Negeri 6 Central Buton (An Experimental Study at the VII Grade Students Outcomes at SMP Negeri 6 Central Buton). This research question is: Are there any effects of YouTube on students' vocabulary mastery at the VII grade students' outcomes of SMP Negeri 6 Central Buton? This study aims to determine YouTube on students' vocabulary mastery among the VII grade students of SMP Negeri 6 Central Buton. The design of this study was a pre-experiment using the One Group Pre-test-Post-test. This research variable consists of two variables: the effect of the Joesin Translation Channel as a free variable and the students' vocabulary mastery as a bound variable. The sample was 26 students. This research instrument was vocabulary tests (pretest and posttest). The data collection technique in this study was to provide pretests, treatments, and posttests. Data on students' English learning outcomes were obtained from the results of the Pretest and Posttest in the form of multiple choice. The data showed an average increase in students' math learning outcomes before applying (39.99%) and (73.71%) after applying to Joesin Translation Channel on YouTube media. Furthermore, the results of testing based on hypothesis testing were carried out statistically one-sample t-test rejected and accepted. With its acceptance, It can be concluded that Joesin Translation Channel is effective in Students' Vocabulary Mastery in improving students' English learning outcomes.